The National Cancer Institute Food Component Research Data Base - Herold, Pauline M. (1988)
The Food Component Research Data Base (FCRDB) is a software package for IBM PC compatible computers that allows a nutritional researcher to perform complex retrievals on a food component data base (currently the USDA Handbook 8 data) using a structured food description language, the FDA/NCI Factored Food Vocabulary (FFV). The FCRDB software is written in the “C” language and uses a windowing interface for ease of use and bitmaps to achieve excellent response times for complex retrievals on a personal computer.